2019
DOI: 10.3390/s19204479
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Based Prediction of Insufficient Herbage Allowance with Automated Feeding Behaviour and Activity Data

Abstract: Sensor technologies that measure grazing and ruminating behaviour as well as physical activities of individual cows are intended to be included in precision pasture management. One of the advantages of sensor data is they can be analysed to support farmers in many decision-making processes. This article thus considers the performance of a set of RumiWatchSystem recorded variables in the prediction of insufficient herbage allowance for spring calving dairy cows. Several commonly used models in machine learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 15 publications
(13 reference statements)
2
22
2
Order By: Relevance
“…However, finding the right parameter or the right combination of parameters remains challenging [ 100 ]. Shafiullah et al [ 101 ] have taken their research a step further and were able to detect herbage shortages in the feeding and activity behaviors of grazing dairy cows and found that rumination chews per day and grazing bites per minute were the best predictors for insufficient grazing [ 101 ]. Machine learning models (support vector machine, random forest, and extreme gradient boosting) hereby performed better than the general linear model did in cross-validation [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, finding the right parameter or the right combination of parameters remains challenging [ 100 ]. Shafiullah et al [ 101 ] have taken their research a step further and were able to detect herbage shortages in the feeding and activity behaviors of grazing dairy cows and found that rumination chews per day and grazing bites per minute were the best predictors for insufficient grazing [ 101 ]. Machine learning models (support vector machine, random forest, and extreme gradient boosting) hereby performed better than the general linear model did in cross-validation [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study by Werner et al [ 17 ] was followed up by Shafiullah et al [ 19 ], who used their data to train models via supervised learning that evaluated sufficiency or insufficiency of herbage allowance on a 24 h basis in grazing dairy cows. The idea was to support farmers in scheduling paddock rotations before cow performance dropped.…”
Section: Introductionmentioning
confidence: 99%
“…The idea was to support farmers in scheduling paddock rotations before cow performance dropped. Using a binary system, Shafiullah et al [ 19 ] developed and validated several prediction approaches based on changes in the cows’ number of rumination chews per day and of their grazing bite frequency, along with six other variables. Among various statistical learning methods, a random forest model (RFM) performed best in classifying the binary feeding status of grazing dairy cows.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations